KAJIAN KOMPENSASI FINANSIAL LANGSUNG DAN TIDAK LANGSUNG TERHADAP KINERJA KARYAWAN PADA PT. BPR ANUGERAHDHARMA YUWANA BANYUWANGI - Elly Wahyu Kosdewata; Nurul Qomariah; Bayu WIjayanti (Universitas Muhammadiyah Jember, 2017)
ABSTRACTThis study aims to determine the relationship of financial compensation on employee performance on the PT.BPR ADY Banyuwangi consists of variable Direct Financial Compensation ( X1 ) , Indirect Financial Compensation ( X2 ) significantly both simultaneously and partially on Employee Performance ( Y ) . To find out which of the above variables are the dominant influence on employee performance . The population in this study are employees of PT.BPR ADY Banyuwangi totaling 69 people . The technical proporsional stratified random sampling . Data collected by distributing questionnaires to the respondents . The scale used is the Likert scale . Results from this study is that simultaneous , variable Direct Financial Compensation ( X1 ) and Indirect Financial Compensation ( X2 ) has a significant influence on employee performance ( Y ) PT.BPR ADY Banyuwangi . Variable Direct Financial Compensation ( X1 ) significantly affects the performance of the employee ( Y ) PT.BPR ADY Banyuwangi . Variable Indirect Financial Compensation ( X2 ) significantly affects the performance of the employee PT.BPR ADY Banyuwangi . Variable Direct Financial Compensation ( X1 ) has a dominant influence on employee performance ( Y ) PT.BPR ADY Banyuwangi Keywords : financial compensation direct , indirect financial compensation , and employee performance .